The impact of psychological distress on quality of care and access to mental health services in cancer survivors - Abdelhadi, Ola (Frontiers in Health Services, 2023)
Our study aimed to examine the impact of psychological distress on the quality of care in cancer survivors using longitudinal panels from the Medical Expenditure Panel Survey data spanning from 2016 to 2019. We compared a sample of cancer survivors with psychological distress (N=176) to a matched sample of cancer survivors without psychological distress (N=2,814). Our findings revealed a higher prevalence of psychological distress among younger survivors, females, individuals with lower incomes, and those with public insurance. Cancer survivors with psychological distress reported more adverse patient experiences compared to those without distress. Specifically, survivors with distress had lower odds of receiving clear explanations of their care (OR 0.40; 95% CI 0.17 to 0.99) and lower odds of feeling respected in expressing their concerns (OR 0.42; 95% CI 0.18 to 0.99) by their healthcare providers. Furthermore, psychological distress was associated with increased healthcare utilization, as evidenced by a higher number of visits (p=0.02). It also correlated with a decrease in healthcare service ratings (p=0.01) and the affordability of mental health services (p<0.01) for cancer survivors. These findings indicate that psychological distress can significantly impact the delivery of healthcare and the patient experience among cancer survivors. Our study underscores the importance of recognizing and addressing the mental health needs of cancer survivors. It provides valuable insights for healthcare professionals to better understand and cater to the mental health needs of this population. Moreover, our findings can inform policymakers in developing strategies to improve access and enhance the quality of mental health services for cancer survivors.